Value on multimodal transport and relationship between shipping performances of maritime industry - Pachateeya, B., Pichit, P., Radasa, N.,; Melan, M., Abaidullah, M., (Opción, 1970)
The aim of this study is to examine service value of multimodal transport and business relationship among the maritime operators towards business performance of cross-border trade in Thailand. Multimodal transport aimed at improving cross-border trade efficiency by transforming the traditional relationship between trading partners and carriers into new cross-border trade partners. The transformed maritime commercial practices had also transformed cross-border trade rules and regulations. Multimodal transport involves more than one transport to move cargo internationally to the desired destination using single window system. The multimodal transport service is meant to reduce transportation cost, safe and reliable. The multimodal transport operators can improve business performance by taking advantage of logistics value through minimizing costs and maximizing profits. In addition, multimodal transport operators need to have strong relationship with transport partners to make the best use of transport mobility and connectivity. This study used quantitative approach using self-administered survey questionnaires by adopting 5-point Likert scale with validated multi-items scales measurement. The sampling technique used was quota sampling to sample of 400 respondents from maritime industry in Thailand. The dependent variable is business performance and the independent variables are multimodal transport service value, logistics service value and logistics relationship. This study used the Structural Equation Model (SEM) and Partial Least Square (PLS) analysis had been used to analyse data collected. The finding the study revealed on the relationship between service values of multimodal transport has significant relationship and impact on business performance of maritime industry in Thailand.